Evaluation of Three-Dimensional Printing-Assisted Laparoscopic Cryoablation of Small Renal Tumors: A Preliminary Report - Jian, Cao; Shuai, Zhu; Mingji, Ye; Kan, Liu; Zhizhong, Liu; Weiqing, Han; Yu, Xie (Urology Journal, 2020)
Purpose: This study aimed to explore the security and feasibility of three-dimensional (3D) printing technology- assisted laparoscopic cryoablation to treat small renal tumors. Patients and Methods: Four patients recruited from our hospital from April 2016 to August 2017 underwent 3D printing technology-assisted laparoscopic cryoablation. Three-dimensional reconstruction technology was used to mimic cryoablation treatment before operations to determine the number of needles needed for the operation and the depth and angle required for needle insertion into the tumor to preserve nephron integrity. CT scans were used to assess the treatment’s efficacy after operation during regular follow-up. Results: The operation was performed successfully in all cases and all patients recovered without major complications. The operation times ranged from 106 to 118 minutes and blood loss ranged from 50 to 100 mL. The follow-up times were between 8-16 months and the mean time was 13.3 months. Follow-up surveys were conducted regularly based on a standard outpatient protocol. Results showed no abnormal reinforcing signals in cryoablation treated areas. Conclusion: 3D printing technology-assisted laparoscopic cryoablation is a feasible method for the treatment of renal tumors and may be a way to better preserve nephrons, especially in elderly patients and/or those with comorbidities.